Elimination of Mn3Ga with Low Crystal Symmetry in Alloying Mn-Ga by Ge Addition - F. Nazari; M. Hakimi; H. Mokhtari; A.S. Esmaeily (Journal of Advanced Materials in Engineering, 2016)
In this paper, milling was investigated as a method for production of Mn-Ga binary alloys and the effect of milling process on phase formation of Mn:Ga samples with 2:1 and 3:1 ratio within 1, 2 and 5 hour milling times was studied. For Mn:Ga samples, according to the results, Mn1.86Ga compound with tetragonal structure and I4/mmm space group was a stable phase. Also, some amounts of  Mn3Ga compound with orthorhombic structure and Cmca space group was observed in the Mn:Ga solution. The effect of Ge addition, with the purpose of  replacing Ge with Ga was also studied in Mn:Ga:Ge (3:0.5:0.5) sample. Although improved magnetic properties is expected with the addition of Ge, but increasing the coercivity was occurred, and saturation magnetization did not change significantly in the studied sample. Ge addition caused elimination of the possibility of formation of asymmetric orthorhombic Mn3Ga phase. In return, two new structures of Mn11Ge8 and MnGaGe were appeared. This phase change was confirmed by studying magnetic behaviour of samples. This behavior can be caused by unbalanced electrostatic forces resulting from Mn-Mn exchange interaction in Mn3Ga orthorhombic structure and substitution of some Ge atoms with Ga.